Salinity and Sugar Content Detection by Wideband Microwave–Based Patch Antenna Sensor - M. N. Rahman; S. M. Taohidul Islam; Md. Maniruzzaman; M. T. Islam (Journal of Electrical and Computer Engineering)
This article studies a dielectric microwave sensor to identify salinity and sugar concentration. The lightweight patch-antenna–based wideband sensor is designed to propagate the electromagnetic wave for the transmission and reception. With a broken-heart-shaped patch, the sensor is printed on common FR4 material. The size of the antenna sensor size is measured in electrical length which is expressed in wavelengths. The sensor occupies an electrical size of 0.29λ × 0.17λ at 2.90 GHz in terms of lower band. The antenna-based microwave sensor attains a bandwidth of 7.80 GHz. In salt and sugar content detection, the sensor operates at 3.50 GHz, 5.80 GHz, and 9.30 GHz, where the reflection coefficients (S11) are −19 dB, −30 dB, and −19.50 dB, respectively, in the free space. The reflection coefficient gradually reduces when the percentages of salt and sugar increase as the dielectric constants of the solution decrease. For the salinity concentration measurement, the microwave sensor shows the sensitivity of 0.095 dB/(mg/mL), 0.1875 dB/(mg/mL), and 0.071 dB/(mg/mL) at 3.50 GHz, 5.80 GHz, and 9.30 GHz, respectively, where, for the sugar content measurement, the microwave sensor shows the sensitivity of 0.086 dB/(mg/mL), 0.216 dB/(mg/mL), and 0.071 dB/(mg/mL), respectively. The patch antenna sensor exhibits remarkable sensitivity to measure the salt and sugar contents in water.